The Effect of Gamification Strategy on Students Motivation and Achievement in Algebra Learning - Wulandari (PT. Anagata Sembagi Education, 2025)
The rapid expansion of remote and hybrid work has urged organizations to adopt new approaches to managing employee performance and motivation. This study aims to examine the role of gamification in remote performance management and its relevance to Generation Alpha as the future workforce. A narrative literature review was conducted by analyzing academic publications and gray literature published between 2020 and 2025. The findings reveal that the implementation of gamification elements such as points, digital rewards, and instant feedback can enhance intrinsic motivation, collaboration, and employee engagement. Its effectiveness largely depends on human-centered design, technological readiness, and adaptive leadership. For Generation Alpha, who have grown up in an interactive and technology-driven environment, gamification represents a highly relevant approach to building meaningful and engaging work experiences. The novelty of this study lies in integrating the concepts of gamification, remote performance management, and Generation Alpha readiness into a comprehensive framework for developing human-centered and sustainable digital work systems.